2002
DOI: 10.1074/jbc.m200418200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Role of the Proline-rich Domain of Nuclear Factor 1-C Splice Variants in DNA Binding and Transactivation

Abstract: Regulation of transcription operates by the combinatorial action of sequence-specific trans-acting factors bound to upstream regulatory regions of promoters and enhancer/silencer regions. The particular linear disposition of these cis-regulatory sequences and their topological organization in chromatin, along with the cellular repertoire of transcription factors results in the formation of gene-and cell-specific constellations of chromatin bound factors. The particular array of proteins on the chromatin target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The prevalent proline, serine, and threonine residues (approximately 20%) might comprise a transcriptional activation domain functionally similar to those described for some mammalian transcription factors (Liu et al. , 2003; Prado et al. , 2002).…”
Section: Molecular Characterization Of Atspl14mentioning
confidence: 63%
“…The prevalent proline, serine, and threonine residues (approximately 20%) might comprise a transcriptional activation domain functionally similar to those described for some mammalian transcription factors (Liu et al. , 2003; Prado et al. , 2002).…”
Section: Molecular Characterization Of Atspl14mentioning
confidence: 63%
“…Previous studies have shown that NF1 stimulates hormone receptor-mediated MMTV transcription both in vitro (17) and in vivo (9,11,12,40,47). Prado et al (40) used Saccharomyces cerevisiae cells to demonstrate that hormoneinduced MMTV transcription is stimulated by the same porcine NF1-C1 protein as that used in our work and that a mutant MMTV promoter having a relaxed chromatin structure displayed a different mode of NF1 and GR synergy. It was thus astonishing to us that NF1 lacked significant effects on MMTV transcription in our experiments using Xenopus oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Exon 6 repeats forming the insertion/deletion polymorphism encode for the proline‐rich region. Such structures, often present in transcription factors, may define the variety and affinity of other cofactors during transcription activity (14–16). Whether and how the insertion/deletion in the IRF5 gene influences gene function remain to be shown.…”
Section: Discussionmentioning
confidence: 99%